Immigrants in 'investment houses' : a qualitative study of immigrant life in the private rented sector in a rural Irish town - Finn, Mairéad (Trinity College (Dublin, Ireland). School of Social Work and Social Policy, 2015)
This thesis explores the housing and settlement experiences of immigrants living in a rural region of Ireland. The research was initiated in 2009, when a period of increased in-migration to Ireland from 1994 - 2009, was coming to an end. A feature of this in-migration to Ireland was that immigrants dispersed beyond the cities, to towns and rural areas around Ireland. This time also signified changes in the policy landscape within housing. Retrenchment in the supply of local authority housing; a growth in the stock of private rented dwellings; developments to regulate the private rented sector; and a move towards meeting housing need via the private rented sector, were events which formed a backdrop to this research.
Keywords: Social Work and Social Policy, Ph.D.; Ph.D. Trinity College Dublin